1988
DOI: 10.1111/j.1464-410x.1988.tb06386.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostatectomy: Patients' Perception and Long‐term Follow‐UP

Abstract: We have reviewed 500 consecutive prostatectomies with a follow-up period of between 5 and 8 years; 184 surviving patients were sent a questionnaire and patients with residual urinary symptoms were interviewed, examined and a flow rate was performed. The operative mortality rate was 0.5%. Patients who presented with retention of urine had a high mortality rate in the first 3 years after the operation. Thirty-six per cent of surviving patients with chronic retention and 24% of those who underwent elective prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
0
2

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 3 publications
2
37
0
2
Order By: Relevance
“…Escalating postoperative complications and longer hospital stays in men with BPH who develop AUR have been reported [ 5 -7 ] . Patients who presented with AUR had a high mortality rate in the fi rst 3 years after prostatectomy [ 8 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Escalating postoperative complications and longer hospital stays in men with BPH who develop AUR have been reported [ 5 -7 ] . Patients who presented with AUR had a high mortality rate in the fi rst 3 years after prostatectomy [ 8 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the indications, risks and benefits have recently been under close scrutiny [1][2][3][4], Although TURP is a successful operation for the great majority of patients, there is associated morbidity and a small failure rate which has prompted the search for alternative thera peutic modalities [2][3][4][5], Heating of the prostate has been advocated for many years, but only became practical with the application of benefit which has been claimed in non-randomized trials is presumed to be due to a cumulative effect from multi ple sessions of low temperature heating.…”
Section: Introductionmentioning
confidence: 99%
“…Bruskewitz et al [13] followed 84 patients for 3 years after transurethral resection of the prostate (TU RP) and found that 75% of the patients claimed to be improved, 18% complained of urge incontinence, and 33% of decreased or absent erection. Alarge retrospective intergroup study [14] revealed that the risk of having a repeat operation was three times higher in the TURP group than in the open surgery group; moreover, long-term, age-specific mortality was higher after TURP than after open surgery [14]. Although surgical treatment of BPH provides rea sonable symptomatic improvement, urologists should look more critically at the late functional outcome of their patients.…”
Section: Introductionmentioning
confidence: 99%